A reliable and feasible qPCR strategy for titrating AAV vectors - Wang, Feng (International Scientific Literature, Inc., 2013)
BACKGROUND: Previous studies have revealed that traditional real-time quantitative PCR (qPCR) underestimates adeno-associated virus (AAV) titer. Because the inverted terminal repeat (ITR) exists in all AAV vectors, the only remaining element from the wild genome could form special configurations to interfere with qPCR titration. To solve this problem, a modified and universal qPCR method was tested and established. MATERIAL/METHODS: In this work, there was a great variation in titration of ssAAV2-EGFP (Enhanced Green Fluorescence Protein) and scAAV2-EGFP genome by traditional qPCR. For ssAAV2-EGFP, the highest titer was found by using the targeting EGFP primers and the lowest titer was measured by those targeting bovine growth hormone polyA element (pBGH) primers. RESULTS: Experimental data were reverse for ssAAV2-EGFP and scAAV2-EGFP. Here we report an improved and universal SmaI qPCR method, based on cleaving all ITRs in AAV2 genome by SmaI with several advantages: (1) impact of all ITRs in ssAAV2 and scAAV2 was dismissed; (2) titers increased remarkably, up to 7-fold, especially for scAAV2; (3) the variation of titers was reduced when different primers were applied. A similar phenomenon was also observed in other ssAAV2 and scAAV2 products when the range of titration was at 3×10(7) to 7×10(9) V.G/μl in this study. CONCLUSIONS: This modified qPCR strategy can increase rAAV’ titer and reduce titration variance, possibly become a universal method for titrating AAV vectors.